Radiation burnthrough measurements to infer opacity at conditions close to the solar radiative zone–convective zone boundary - Hoarty,DJ; Morton,J; Rougier,JC; Rubery,M; Opachich,YP; Swatton,D; Richardson,S; Heeter,RF; McLean,K; Rose,SJ; Perry,TS; Remington,B (Physics of Plasmas, 2023)
Recent measurements at the Sandia National Laboratory of the x-ray transmission of iron plasma have inferred opacities much higher than predicted by theory, which casts doubt on modeling of iron x-ray radiative opacity at conditions close to the solar convective zone-radiative zone boundary. An increased radiative opacity of the solar mixture, in particular iron, is a possible explanation for the disagreement in the position of the solar convection zone-radiative zone boundary as measured by helioseismology and predicted by modeling using the most recent photosphere analysis of the elemental composition. Here, we present data from radiation burnthrough experiments, which do not support a large increase in the opacity of iron at conditions close to the base of the solar convection zone and provide a constraint on the possible values of both the mean opacity and the opacity in the x-ray range of the Sandia experiments. The data agree with opacity values from current state-of-the-art opacity modeling using the CASSANDRA opacity code.